Kajian Peningkatan Kinerja Pegawai Negeri Sipil pada Inspektorat Kota Manado - Wilar, Conny; Lumolos, Johny (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: Purpose of the research to find out and examine how to increase the performance of the Inspectorate of Civil Servants in Manado City. The research method used is qualitative research by collecting data through interviews, observation and documentation. Informant obtained based on the consideration of researchers, those who are considered to provide an objective and accurate information in accordance with research problems. Informants in this study amounted to 15 people consisting of 12 employees of the Inspectorate Manado City, 3 employees SKPD other related work to the City Inspectorate Manado. The results showed that there was an increase in civil servants' performance in Manado City Inspectorate than in previous years. In general, work motivation, work disciplines and skills that support the work performance of employees has increased, but not maximized due to the lack of standard operating procedures (SOP) is the standard / reference for each job in the Inspectorate and the absence of a functional energy auditors who are experts and competence in the field of inspection. From the research it can be concluded that the quality and quantity of work of the Inspectorate staff in Manado city is good enough but not maximized due to the absence of standard operating procedures (SOP) and the absence of a functional energy auditor. Motivation to work is good and highly motivated, disciplined and skilled labor inspectorate staff working Manado city is good and increasing. In order to increase employee performance, recommended the drafting of standard operating procedures need to be the basis / reference of any work carried out so that the end result to be more qualified jobs, and the need for functional staff auditor truly skilled and competent in the field of inspection so that they become power ready to use. The motivation of the subordinate leaders must continue to be provided, further momentum in disciplines that have been implemented in 2012 can serve as cultural and permanent program that can maintain the discipline of work, especially in Manado City Inspectorate. There should also have the expertise and skills training so that employees continually kept up to date skills and knowledge in the performance.Keywords : Performance, Motivation, Dicipline, Skill